The Herschel-ATLAS data release 2. Paper II. Catalogs of far-infrared and submillimeter sources in the fields at the south and north Galactic poles - Maddox, S.J.; Valiante, E.; Cigan, P.J.; Dunne, L.; Eales, S.; Smith, M.W.L.; Dye, S.; Furlanetto, C.; Ibar, E.; Zotti, G. de; Millard, J.S.; Bourne, N.; et al. (American Astronomical Society, 2018)
The Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS) is a survey of 660 deg2 with the PACS and SPIRE cameras in five photometric bands: 100, 160, 250, 350, and 500 μm. This is the second of three papers describing the data release for the large fields at the south and north Galactic poles (NGP and SGP). In this paper we describe the catalogs of far-infrared and submillimeter sources for the NGP and SGP, which cover 177.1 deg2 and 303.4 deg2, respectively. The catalogs contain 118,908 sources for the NGP field and 193,527 sources for the SGP field detected at more than 4σ significance in any of the 250, 350, or 500 μm bands. The source detection is based on the 250 μm map, and we present photometry in all five bands for each source, including aperture photometry for sources known to be extended. The rms positional accuracy for the faintest sources is about 2.4 arcsec in both R.A. and decl. We present a statistical analysis of the catalogs and discuss the practical issues—completeness, reliability, flux boosting, accuracy of positions, accuracy of flux measurements—necessary to use the catalogs for astronomical projects.